Data input and content exploration in scenarios with restrictions - Pedrosa, Diogo de Carvalho (2014)
As technology evolves, new devices and interaction techniques are developed. These transformations create several challenges in terms of usability and user experience. Our research faces some challenges for data input or content exploration in scenarios with restrictions. It is not our intention to investigate all possible scenarios, but we deeply explore a broad range of devices and restrictions. We start with a discussion about the use of an interactive coffee table for exploration of personal photos and videos, also considering a TV set as an additional screen. In a second scenario, we present an architecture that offers to interactive digital TV (iDTV) applications the possibility of receiving multimodal data from multiple devices. Our third scenario concentrates on supporting text input for iDTV applications using a remote control, and presents an interface model based on multiple input modes as a solution. In the last two scenarios, we continued investigating better ways to provide text entry; however, our restriction becomes not using the hands, which is the kind of challenge faced by severely motor-disabled individuals. First, we present a text entry method based on two input symbols and an interaction technique based on detecting internal and external heel rotations using an accelerometer, for those who keep at least a partial movement of a leg and a foot. In the following scenario, only the eyes are required. We present an eye-typing technique that recognizes the intended word by weighting length and frequency of all possible words formed by filtering extra letters from the sequence of letters gazed by the user. The exploration of each scenario in depth was important to achieve the relevant results and contributions. On the other hand, the wide scope of this dissertation allowed the student to learn about several technologies and techniques.